STUDI KELAYAKAN WAKAF PRODUKTIF - Aji, Gunawan (Kopertais Wilayah X Jawa Tengah, 2015)
AbstractMosque as one of the objects of waqf can provide added value if managed productively. Land of the mosque can be used for a variety productive activities according to the principles of Islam. ! is study analyzes the aspects of marketing and